H2S Loss through Nalophan™ Bags: Contributions of Adsorption and Diffusion - Lidia Eusebio; Laura Capelli; Selena Sironi (The Scientific World Journal)
Hydrogen-sulfide (H2S) is a molecule of small dimensions typically present in the odor emissions from different plants. The European Standard EN 13725:2003 set a maximum storage time allowed of 30 hours, during which the sampling bag has to maintain the mixture of odorants with minimal changes. This study investigates the H2S losses through Nalophan bags and it shows that nonnegligible losses of H2S can be observed. The percent H2S loss after 30 hrs with respect to the initial concentration is equal to 33%  ± 3% at a relative humidity of 20% and equal to 22%  ± 1% at a relative humidity of 60%. The average quantity of adsorbed H2S at 30 h is equal to 2.17 105 gH2S/gNalophan at a storage humidity of 20% and equal to 1.79 105 gH2S/gNalophan at a storage humidity of 60%. The diffusion coefficients of H2S through Nalophan, for these two humidity conditions tested, are comparable (i.e., 7.5 10−12 m2/sec at 20% humidity and 6.6 10−12 m2/sec at 60% humidity).